Analisis Daya Saing Ekspor Minyak Kelapa Mentah (Crude Coconut Oil) Sulawesi Utara - Tambunan, Agustina Lantarida; Katiandagho, Theodora M.; Laoh, Olly E.H. (AGRI-SOSIOEKONOMI, 2024)
This research aims to analyze the power of raw coconut oil products in northern Sulawesi in 2018-2022. This study was held for four months, which is from April to July 2023. This research site is located in North Sulawesi. As for data obtained via secondary data taken from the body of the Central statistic North Sulawesi and central statistics center, Industrial services and trade in North Sulawesi, journals and the Internet. Variables used in research are the export value of raw coconut North Sulawesi and Indonesia (million US$) period of 2018-2022, non-migas export value North Sulawesi and Indonesia (million US$) period of 2018-2022. This research uses a revealed comparative advance (RCA) method to measure comparative and export competition (ECI) power to measure competitive power. The results of this study show that the comparative competitiveness of North Sulawesi crude coconut oil in 2018 until 2022 has a competitive advantage because the RCA value of North Sulawesi crude coconut oil is more than one. Whereas for the competitive competitiveness of North Sulawesi crude coconut oil only has competitive in 2021 because the ECI value is more than one. For the year 2018, 2019, 2020, and 2022 have no competitive advantage because eci value is below one.